Solid-state polymer electrolyte and method for preparing a battery therefrom
Patent Information
- Application Number
- CN202611191181.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-08-07
AI Technical Summary
Existing polyoxyethylene solid polymer electrolytes have low ionic conductivity at room temperature, low lithium-ion transference number, and difficulty in balancing mechanical strength and ionic conductivity. Furthermore, they have poor interfacial compatibility with the positive and negative electrodes.
A fixed anionic-ether oxygen synergistic transport component is adopted. A core-graft layer structure is formed by grafting polymer chains onto a nano-silica inorganic support core. Combined with polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer and cross-linking network, a semi-interpenetrating network structure is formed. Lithium difluorooxalate borate and succinic anion are added to improve interfacial compatibility.
It significantly improves the lithium-ion transference number, reduces concentration polarization during charge and discharge, improves the rate performance and cycle stability of the battery, and enhances mechanical strength and interface stability.
Smart Images

Figure CN122696790B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery materials technology, specifically to a solid polymer electrolyte and a method for preparing the battery thereon. Background Technology
[0002] Solid-state lithium batteries are considered a key development direction for next-generation energy storage technology due to their high energy density and high safety. Solid-state polymer electrolytes have attracted widespread attention in the solid-state battery field due to their excellent flexibility, processability, and interfacial contact properties. Among them, vinyl oxide solid-state polymer electrolytes have become one of the most extensively studied systems due to their good solubility for lithium salts and good compatibility with lithium metal. However, the ionic conductivity of vinyl oxide electrolytes at room temperature is typically only 10⁻⁶. -6 Up to 10 -5 The S / cm range is insufficient to meet practical application requirements; moreover, its ion conduction mainly relies on the movement of polyethylene oxide chain segments, resulting in a low lithium-ion transference number, typically below 0.3, which easily leads to concentration polarization and lithium dendrite growth. In addition, pure polyethylene oxide has insufficient mechanical strength and a narrow electrochemical window, limiting its application in matching high-voltage cathode materials.
[0003] To overcome the aforementioned shortcomings, existing technologies modify polyoxyethylene electrolytes by introducing inorganic nanofillers, blending with other polymers, adding plasticizers, or constructing cross-linked networks. Inorganic nanofillers such as silica and alumina can improve mechanical strength and ionic conductivity to some extent, but interfacial compatibility issues between the inorganic and organic phases often lead to filler agglomeration, and simple physical blending is insufficient to achieve stable dispersion of the fillers during long-term cycling. Plasticizers such as succinic anionyl nitrile can effectively improve ionic conductivity, but excessive addition can sacrifice mechanical properties and thermal stability. Constructing chemical cross-linked networks can improve mechanical strength, but excessive cross-linking can inhibit polymer chain movement, thereby reducing ion conduction efficiency. Therefore, how to synergistically improve the ionic conductivity, lithium-ion transference number, and electrochemical stability of solid polymer electrolytes while ensuring good mechanical properties, and simultaneously improve their interfacial compatibility with the positive and negative electrodes, is a pressing technical problem to be solved in this field. Summary of the Invention
[0004] The purpose of this invention is to address the problems of low room temperature ionic conductivity, low lithium-ion transference number, difficulty in balancing mechanical strength and ion conduction performance, and poor interface stability in existing solid polymer electrolytes, and to provide a solid polymer electrolyte and its battery preparation method.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is: a solid polymer electrolyte, wherein the total mass of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer in the solid polymer electrolyte is 100 parts, wherein polyethylene oxide comprises 60-80 parts by mass and polyvinylidene fluoride-hexafluoropropylene copolymer comprises 20-40 parts by mass; based on the total mass of 100 parts of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer, the solid polymer electrolyte further comprises the following components in parts by mass: lithium bis(trifluoromethanesulfonyl)imide 25-45 parts, succinate 6-18 parts, polyethylene glycol diacrylate 5-12 parts, photoinitiator 0.15-0.50 parts, lithium difluorooxalate borate 1-4 parts, and fixed anionic-ether oxygen synergistic transport component 6-18 parts.
[0006] Furthermore, the fixed anion-ether oxygen synergistic transport component is made from the following raw materials in parts by weight: 100 parts of nano silica, 5-10 parts of 3-methacryloyloxypropyltrimethoxysilane, 25-45 parts of sodium p-styrene sulfonate, 20-35 parts of polyethylene glycol methyl ether methacrylate, and 0.5-1.0 parts of ammonium persulfate.
[0007] Furthermore, the fixed anion-ether oxygen synergistic transport component has a core-graft layer structure with nano-silica as the inorganic support core and polymer chains grafted onto the surface of the inorganic support core as the ion transport layer. The polymer chains are composed of lithium p-styrene sulfonate structural units and polyethylene glycol methyl ether methacrylate structural units. The sulfonate group in the lithium p-styrene sulfonate structural unit is fixed on the polymer chain, and the coordinating ion of the sulfonate group is a lithium ion. The polyether side chains in the polyethylene glycol methyl ether methacrylate structural unit are distributed between the lithium sulfonate structural units.
[0008] Furthermore, the number average molecular weight of the polyethylene oxide is 300,000 to 1,000,000.
[0009] Furthermore, the mass fraction of hexafluoropropylene structural units in the polyvinylidene fluoride-hexafluoropropylene copolymer is 8%-20%.
[0010] Furthermore, the number average molecular weight of the polyethylene glycol diacrylate is 400-1000; Furthermore, the number average molecular weight of the polyethylene glycol methyl ether methacrylate is 400-600.
[0011] Furthermore, the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone.
[0012] Furthermore, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalateborate is 8:1 to 25:1.
[0013] Furthermore, the ratio of the total molar amount of lithium ions contained in the lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate to the total molar amount of ether oxygen atoms contained in the polyethylene oxide structural unit in the solid polymer electrolyte is 1:7 to 1:20.
[0014] Furthermore, the content of lithium sulfonate groups in the fixed anion-ether oxygen synergistic transport component is 0.40-1.20 mmol / g, and the molar ratio of polyether oxygen atoms to lithium sulfonate groups in the ion transport layer is 2∶1-4∶1.
[0015] Furthermore, the preparation method of the anion-ether oxygen synergistic transport component includes the following steps: A1. Dry nano-silica at 110-130℃ and a vacuum degree not exceeding 500Pa for 3-5 hours. Add 100 parts by weight of the dried nano-silica to a mixture of anhydrous ethanol and deionized water in a mass ratio of 95:5, so that the mass ratio of nano-silica to the mixture is 1:10-1:20. Add 5-10 parts by weight of 3-methacryloyloxypropyltrimethoxysilane. Adjust the pH of the system to 4.2-4.8 with a 10% aqueous acetic acid solution. React at 55-65℃ and 400-700 r / min for 3-5 hours. After centrifugation, wash three times with anhydrous ethanol and dry at 60-75℃ and a vacuum degree not exceeding 1000Pa for 8-12 hours to obtain modified nano-silica containing surface alkenyl groups.
[0016] A2. Add 100 parts by mass of the modified nano-silica containing surface alkenyl groups to deionized water bubbled with nitrogen for 20-40 min, so that the mass ratio of the modified nano-silica to deionized water is 1:8-1:15. Add 25-45 parts by mass of sodium p-styrene sulfonate and 20-35 parts by mass of polyethylene glycol methyl ether methacrylate. Disperse at 25-35℃ and 500-800 r / min for 30-60 min. Continue to purge with nitrogen and heat the system to 60-70℃. Add 0.5-1.0 parts by mass of ammonium persulfate. Perform graft copolymerization reaction at 60-70℃ and 400-600 r / min for 4-8 h. Centrifuge and wash with deionized water until the absorbance of the washing solution at 254 nm wavelength is not higher than 0.05 to obtain sodium sulfonate-polyether-linked nano-silica.
[0017] A3. Add the sodium sulfonate-polyether-linked nano-silica to a 0.5-1.0 mol / L hydrochloric acid aqueous solution, making the mass ratio of sodium sulfonate-polyether-linked nano-silica to hydrochloric acid aqueous solution 1:10-1:20. Perform ion exchange at 25-40℃ and 300-500 r / min for 2-4 hours. After centrifugation, repeat the ion exchange operation once. Wash with deionized water until the chloride ion mass fraction in the washing solution is no higher than 0.01%, to obtain hydrogen sulfonate-polyether chain. Grafted nano-silica: The sulfonate-type polyether-linked nano-silica is dispersed in deionized water, and a lithium hydroxide aqueous solution with a concentration of 0.1-0.5 mol / L is added dropwise at 25-40℃ and 300-500 r / min until the pH of the system is 6.5-7.5. The mixture is stirred for 2-4 h, centrifuged and washed with deionized water, and dried at 60-80℃ and a vacuum degree not exceeding 500 Pa for 12-20 h to obtain the fixed anion-ether oxygen synergistic transport component.
[0018] This invention also provides a method for preparing a solid polymer electrolyte, comprising the following steps: S1. The polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and the fixed anionic-ether oxygen synergistic transport component are dried at 60-80℃ and under a vacuum degree not exceeding 500Pa for 12-24h respectively.
[0019] S2. According to the above-mentioned mass fractions, add polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer to a mixed solvent composed of N,N-dimethylformamide and acetonitrile in a mass ratio of 1:0.8-1:1.5, so that the total mass fraction of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is 8%-18%, and stir for 4-8 hours at 45-60℃ and 400-700r / min to obtain a polymer solution.
[0020] S3. Lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, and succinate are added to the polymer solution and stirred at 45-60℃ and 400-700 r / min for 2-4 h. The fixed anionic-ether oxygen synergistic transport component is added and ultrasonically dispersed at 300-600 W and 35-45 kHz for 20-40 min. Then, polyethylene glycol diacrylate and photoinitiator are added and stirred at 300-500 r / min for 30-60 min under light-protected conditions to obtain the electrolyte slurry.
[0021] S4. The electrolyte slurry is coated onto the surface of the release substrate, with a wet film thickness of 150-500 μm, and dried at 40-55℃ for 4-8 hours. Under nitrogen protection, both sides of the film are irradiated with ultraviolet light at a wavelength of 365 nm and an irradiation intensity of 10-30 mW / cm2 for 5-15 minutes to cause cross-linking polymerization of polyethylene glycol diacrylate. The cross-linked film material is peeled off from the surface of the release substrate and dried at 40-50℃ and a vacuum degree not exceeding 300 Pa for 12-24 hours to obtain a solid polymer electrolyte membrane.
[0022] Furthermore, after adding the fixed anionic-ether oxygen synergistic transport component in step S3, the mixture is first stirred at 800-1200 r / min for 30-60 min, and then ultrasonically dispersed; the solid polymer electrolyte membrane obtained in step S4 has a thickness of 30-120 μm, and the gel fraction of the solid polymer electrolyte membrane at 25℃ is 75%-95%.
[0023] A solid-state lithium battery includes a positive electrode, a negative electrode, and a solid polymer electrolyte membrane disposed between the positive electrode and the negative electrode. The solid polymer electrolyte membrane is the aforementioned solid polymer electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The negative electrode includes a negative current collector and a negative active material layer or a lithium metal layer disposed on the surface of the negative current collector.
[0024] Furthermore, the positive electrode active material layer comprises 70-90 parts by weight of positive electrode active material, 3-10 parts by weight of conductive agent, 3-10 parts by weight of binder, and 5-15 parts by weight of the above-mentioned solid polymer electrolyte; the positive electrode active material is one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, or lithium nickel cobalt aluminum oxide, and the negative electrode active material in the negative electrode active material layer is one of graphite, silicon-carbon composite material, or lithium titanate.
[0025] A method for preparing a solid-state lithium battery includes the following steps: B1. Dry the positive electrode and negative electrode at 80-120℃ and a vacuum degree not exceeding 500Pa for 8-16 hours respectively, and dry the solid polymer electrolyte membrane at 40-50℃ and a vacuum degree not exceeding 300Pa for 8-12 hours. When the negative electrode active material layer of the negative electrode is a lithium metal layer, the lithium metal sheet is not dried and can be used directly in a dry environment with a dew point not exceeding -40℃.
[0026] B2. In a dry environment with a dew point not higher than -40°C, the positive electrode, solid polymer electrolyte membrane, and negative electrode are stacked in the order of positive electrode, solid polymer electrolyte membrane covering the positive electrode active material layer and the negative electrode active material layer or the lithium metal layer.
[0027] B3. The stacked positive electrode, solid polymer electrolyte membrane and negative electrode are hot-pressed at 60-90℃ and 2-8MPa for 5-20 minutes to obtain the battery cell.
[0028] B4. In a dry environment with a dew point not higher than -40°C, the battery cell is placed into a battery casing or aluminum-plastic film packaging and sealed. It is then left to stand at 45-65°C for 6-12 hours to obtain a solid-state lithium battery.
[0029] The solid-state lithium battery described in this invention is applicable to electric vehicles and other motor vehicles, but excludes the production and manufacturing of fuel cell vehicles.
[0030] Compared with the prior art, the beneficial effects of the present invention are: By introducing a fixed anion-ether oxygen synergistic transport component, sulfonate anions are covalently fixed on the grafted polymer chain. Lithium ions, as the main migratable charge carriers, significantly increase the lithium ion transference number and reduce concentration polarization during charge and discharge, thereby improving the rate performance and cycle stability of the battery.
[0031] The polyether side chains in the fixed anion-ether-oxygen synergistic conduction component form synergistic ion conduction channels with the polyethylene oxide molecular chains in the semi-interpenetrating network matrix. The polyether side chains provide rapid lithium ion coordination-discoordination sites, and the fixed anion groups promote lithium salt dissociation and guide lithium ion directional migration through electrostatic interaction, thereby significantly improving the room temperature ionic conductivity of the electrolyte.
[0032] The continuous polymer phase formed by polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer and the crosslinked network formed by the photopolymerization of polyethylene glycol diacrylate constitute a semi-interpenetrating network structure. This structure has both excellent mechanical strength and flexibility, effectively inhibiting the penetration growth of lithium dendrites. At the same time, the nano-silica inorganic support core in the anion-ether oxygen synergistic conduction component further enhances the dimensional stability and thermal stability of the electrolyte membrane.
[0033] The introduction of lithium difluorooxalate borate can form a stable solid electrolyte interface film on the negative electrode surface. Combined with the solubilizing effect of succinate on lithium salt, it significantly reduces the interfacial impedance between the electrolyte and the lithium metal negative electrode, and improves the interfacial stability during long-term cycling. Attached Figure Description
[0034] Figure 1 The Fourier transform infrared (FTIR) spectrum of the preparation process of the fixed anion-ether oxygen synergistic transport component prepared in Example 1 of this invention.
[0035] Figure 2 This is a curve showing the change in ionic conductivity of the solid polymer electrolyte membrane prepared in Example 1 of the present invention as a function of temperature.
[0036] Figure 3 This is a transmission electron microscope (TEM) image of the fixed anion-ether oxygen synergistic transport component prepared in Example 1 of the present invention. Detailed Implementation
[0037] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] The specifications of the main raw materials used in the embodiments of this invention are as follows: the nano-silica is fumed silica with a specific surface area of 20-60 m². 2 / g, purity not less than 99.8%.
[0039] Both lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate are battery grade, with a moisture content of no more than 100 ppm.
[0040] The purity of succinic anion is not less than 99%, and the moisture content is not more than 200 ppm.
[0041] All other raw materials were commercially available analytical grade reagents.
[0042] Example 1
[0043] (1) Preparation of the fixed anion-ether oxygen synergistic transport component: A1. Nano-silica with a median particle size of 100 nm was dried at 120 °C and a vacuum of 400 Pa for 4 h. 100 parts by mass of the dried nano-silica were added to a mixture of anhydrous ethanol and deionized water at a mass ratio of 95:5, making the mass ratio of nano-silica to the mixture 1:15. 7.5 parts by mass of 3-methacryloyloxypropyltrimethoxysilane were added, and the pH of the system was adjusted to 4.5 using a 10% aqueous acetic acid solution. The mixture was reacted at 60 °C and 600 r / min for 4 h. After centrifugation, the nano-silica was washed three times with anhydrous ethanol and dried at 70 °C and a vacuum of 800 Pa for 10 h to obtain modified nano-silica containing surface alkenyl groups.
[0044] A2. 100 parts by mass of the modified nano-silica containing surface alkenyl groups were added to deionized water bubbled with nitrogen for 30 min, so that the mass ratio of the modified nano-silica to deionized water was 1:12. 35 parts by mass of sodium p-styrene sulfonate and 28 parts by mass of polyethylene glycol methyl ether methacrylate with a number average molecular weight of 500 were added. The mixture was dispersed at 30°C and 700 r / min for 45 min. Nitrogen gas was continued to be introduced, and the system was heated to 65°C. 0.75 parts by mass of ammonium persulfate were added, and the graft copolymerization reaction was carried out at 65°C and 500 r / min for 6 h. The mixture was centrifuged and washed with deionized water until the absorbance of the washing liquid at a wavelength of 254 nm was 0.04, to obtain sodium sulfonate-polyether-linked nano-silica.
[0045] A3. The sodium sulfonate-polyether-linked nano-silica was added to a 0.8 mol / L hydrochloric acid aqueous solution, making the mass ratio of sodium sulfonate-polyether-linked nano-silica to hydrochloric acid aqueous solution 1:15. Ion exchange was performed at 35℃ and 400 r / min for 3 h. After centrifugation, the ion exchange operation was repeated once. The nano-silica was washed with deionized water until the chloride ion mass fraction in the washing solution was 0.005%, to obtain hydrogen sulfonate-polyether-linked nano-silica. The hydrogen sulfonate-polyether-linked nano-silica was dispersed in deionized water, and a 0.3 mol / L lithium hydroxide aqueous solution was added dropwise at 35℃ and 400 r / min until the pH of the system reached 7.0. The mixture was stirred for 3 h, centrifuged, washed with deionized water, and dried at 70℃ and 400 Pa for 16 h to obtain the fixed anion-ether oxygen synergistic transport component. The determination showed that the content of lithium sulfonate groups in the fixed anion-ether oxygen synergistic transport component was 0.85 mmol / g, and the molar ratio of polyether oxygen atoms to lithium sulfonate groups in the ion transport layer was approximately 2.8:1.
[0046] (2) Preparation of solid polymer electrolytes: S1. Polyethylene oxide with a number average molecular weight of 600,000, polyvinylidene fluoride-hexafluoropropylene copolymer with a hexafluoropropylene structural unit mass fraction of 12%, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and the above-mentioned fixed anionic-ether oxygen synergistic transport component were dried at 70°C and a vacuum degree of 400 Pa for 18 h.
[0047] S2. Add 70 parts by mass of polyethylene oxide and 30 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer to a mixed solvent composed of N,N-dimethylformamide and acetonitrile in a mass ratio of 1:1.1, so that the total mass fraction of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is 12%. Stir at 50°C and 600 r / min for 6 h to obtain a polymer solution.
[0048] S3. Add 35 parts by mass of lithium bis(trifluoromethanesulfonyl)imide, 2.5 parts by mass of lithium difluorooxalateborate, and 12 parts by mass of succinic anion to the polymer solution and stir for 3 hours at 50°C and 600 r / min. Add 12 parts by mass of the above-mentioned fixed anionic-ether oxygen synergistic transport component, stir at 1000 r / min for 45 minutes, then ultrasonically disperse at 450 W and 40 kHz for 30 minutes. Then add 8 parts by mass of polyethylene glycol diacrylate with a number average molecular weight of 600 and 0.30 parts by mass of 2-hydroxy-2-methyl-1-phenylpropanone, and stir at 400 r / min for 45 minutes under light-protected conditions to obtain an electrolyte slurry. The mass ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalateborate is 14:1, and the ratio of the total molar amount of lithium ions contained in lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate to the total molar amount of polyether oxygen atoms in the solid polymer electrolyte is 1:11.4.
[0049] S4. The electrolyte slurry is coated onto the surface of a polyethylene terephthalate release substrate, with a wet film thickness of 500 μm, and dried at 50°C for 6 hours; under nitrogen protection, an irradiation with a wavelength of 365 nm and an irradiation intensity of 20 mW / cm² is applied. 2 The membrane was irradiated with ultraviolet light on both sides for 10 minutes to induce cross-linking polymerization of polyethylene glycol diacrylate. The cross-linked membrane material was then peeled off from the release substrate and dried at 45°C and a vacuum of 200 Pa for 18 hours to obtain a solid polymer electrolyte membrane. The thickness of this solid polymer electrolyte membrane was approximately 60 μm, and the gel fraction at 25°C was 88%.
[0050] Figure 1 The infrared absorption characteristics of pristine silica, vinyl-modified silica, sodium sulfonate-polyether-linked silica, and the finally fixed anionic-ether oxygen synergistic transport component were compared. Pristine silica showed the best absorption at approximately 3400 cm⁻¹. -1 A broad peak appears at approximately 1100 cm⁻¹, caused by surface hydroxyl groups and adsorbed water. -1 It exhibits a strong Si—O—Si antisymmetric stretching vibration peak at approximately 800 cm⁻¹. -1 and 470cm -1 Characteristic absorptions of the silicon-oxygen framework were observed nearby; after silane coupling modification, the absorption was approximately 2920 cm⁻¹. -1 The aliphatic C-H stretching peak at approximately 1720 cm⁻¹ -1 The appearance or enhancement of the C=O absorption peak at the ester group indicates that the alkenyl silane has been attached to the silica surface. After grafting sodium p-styrene sulfonate and polyethylene glycol methyl ether methacrylate, the absorption peak at approximately 1600-1500 cm⁻¹... -1 Aromatic ring skeletal vibrations occur within this range, approximately 1180-1040 cm⁻¹. -1The S=O vibration of sulfonate and the C—O—C vibration of polyether were significantly enhanced and overlapped with the Si—O—Si peak. After acid exchange and neutralization with lithium hydroxide, the main organic grafting peaks were still retained, and some sulfonate absorption peaks were slightly shifted, indicating that the ion exchange did not destroy the grafting chain structure, and finally a silica grafting system containing fixed lithium sulfonate anions and polyether side chains was formed.
[0051] Figure 2 This indicates that the ionic conductivity of the solid polymer electrolyte membrane continuously increases with temperature from 25℃ to 80℃, approximately from 10... -5 S·cm -1 The magnitude increased to nearly 10 -3 S·cm -1 The magnitude of the measured values is significant, and the test points are generally distributed along the dashed line fitting curve on a semi-logarithmic coordinate system, exhibiting a relatively obvious thermally activated ion conduction characteristic. Heating enhances the local mobility of polyethylene oxide and grafted polyether segments, shortens the coordination-discoordination time of lithium ions between ether oxygen coordination sites, and simultaneously increases the degree of lithium salt dissociation. This allows lithium ions to migrate along continuous polyether channels and local conduction sites near fixed anions, thus gradually increasing conductivity. The relatively small error bars at each temperature point indicate good test repeatability and membrane system uniformity.
[0052] Figure 3 The medium-sized particles are nearly spherical in shape, with a dark-colored, nano-sized silica inorganic core at the center, exhibiting low electron transmittance. A continuous, lighter-colored coating region is observed around the particles, corresponding to the lithium sulfonate-polyether copolymer chain ion-conducting layer grafted onto the silica surface, displaying a clear "dark inorganic core - light-colored grafted layer" core-grafted layer morphology. Most particles have discernible boundaries and are relatively uniformly distributed, with only localized contact or slight aggregation between particles, indicating that the surface-grafted polymer chains reduce the direct hydrogen bonding and aggregation tendency between silica particles to some extent. A few irregular light gray fragments and tiny black dots in the field of view may originate from free polymers, incompletely removed trace impurities, or sample preparation deposits.
[0053] Example 2
[0054] (1) Preparation of the fixed anion-ether oxygen synergistic transport component: A1. Nano-silica with a median particle size of 50 nm was dried at 110 °C and a vacuum of 500 Pa for 3 h. 100 parts by mass of the dried nano-silica were added to a mixture of anhydrous ethanol and deionized water at a mass ratio of 95:5, making the mass ratio of nano-silica to the mixture 1:10. 5 parts by mass of 3-methacryloyloxypropyltrimethoxysilane were added, and the pH of the system was adjusted to 4.2 using a 10% aqueous acetic acid solution. The mixture was reacted at 55 °C and 700 r / min for 3 h. After centrifugation, the nano-silica was washed three times with anhydrous ethanol and dried at 60 °C and a vacuum of 1000 Pa for 8 h to obtain modified nano-silica containing surface alkenyl groups.
[0055] A2. 100 parts by mass of the modified nano-silica containing surface alkenyl groups were added to deionized water bubbled with nitrogen for 20 min, so that the mass ratio of the modified nano-silica to deionized water was 1:8. 25 parts by mass of sodium p-styrene sulfonate and 20 parts by mass of polyethylene glycol methyl ether methacrylate with a number average molecular weight of 400 were added, and the mixture was dispersed at 25°C and 800 r / min for 30 min. Nitrogen gas was continued to be introduced, and the system was heated to 60°C. 0.5 parts by mass of ammonium persulfate were added, and the graft copolymerization reaction was carried out at 60°C and 600 r / min for 4 h. The mixture was centrifuged and washed with deionized water until the absorbance of the washing liquid at a wavelength of 254 nm was 0.04, to obtain sodium sulfonate-polyether-linked nano-silica.
[0056] A3. The sodium sulfonate-polyether-linked nano-silica was added to a 0.5 mol / L hydrochloric acid aqueous solution, making the mass ratio of sodium sulfonate-polyether-linked nano-silica to hydrochloric acid aqueous solution 1:10. Ion exchange was performed at 25℃ and 500 r / min for 2 h. After centrifugation, the ion exchange operation was repeated once. The nano-silica was washed with deionized water until the chloride ion mass fraction in the washing solution was 0.008%, to obtain hydrogen sulfonate-polyether-linked nano-silica. The hydrogen sulfonate-polyether-linked nano-silica was dispersed in deionized water, and a 0.1 mol / L lithium hydroxide aqueous solution was added dropwise at 25℃ and 500 r / min until the pH of the system reached 6.8. The mixture was stirred for 2 h, centrifuged, washed with deionized water, and dried at 60℃ and 500 Pa for 12 h to obtain the fixed anion-ether oxygen synergistic transport component. The content of lithium sulfonate groups in the fixed anion-ether oxygen synergistic transport component was determined to be 0.77 mmol / g, and the molar ratio of polyether oxygen atoms to lithium sulfonate groups in the ion transport layer was approximately 2.5:1.
[0057] (2) Preparation of solid polymer electrolytes: S1. Polyethylene oxide with a number average molecular weight of 300,000, polyvinylidene fluoride-hexafluoropropylene copolymer with a hexafluoropropylene structural unit mass fraction of 8%, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalateborate and the above-mentioned fixed anionic-ether oxygen synergistic transport component were dried at 60°C and a vacuum degree of 500 Pa for 24 h.
[0058] S2. Add 80 parts by mass of polyethylene oxide and 20 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer to a mixed solvent composed of N,N-dimethylformamide and acetonitrile in a mass ratio of 1:0.8, so that the total mass fraction of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is 8%. Stir at 45°C and 700 r / min for 8 h to obtain a polymer solution.
[0059] S3. Add 25 parts by mass of lithium bis(trifluoromethanesulfonyl)imide, 1 part by mass of lithium difluorooxalate borate, and 6 parts by mass of succinic anion to the polymer solution and stir at 45°C and 700 r / min for 4 h. Add 6 parts by mass of the above-mentioned fixed anionic-ether oxygen synergistic transport component, stir at 800 r / min for 30 min, then ultrasonically disperse at 300 W and 35 kHz for 40 min. Then add 5 parts by mass of polyethylene glycol diacrylate with a number average molecular weight of 1000 and 0.15 parts by mass of 2-hydroxy-2-methyl-1-phenylpropanone, and stir at 300 r / min for 60 min under light-protected conditions to obtain an electrolyte slurry. The mass ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalate borate is 25:1, and the ratio of the total molar amount of lithium ions in lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalate borate to the total molar amount of polyether oxygen atoms in the solid polymer electrolyte is 1:19.3.
[0060] S4. The electrolyte slurry is coated onto the surface of a polyethylene terephthalate release substrate, with a wet film thickness of 450 μm, and dried at 40°C for 8 hours. Under nitrogen protection, both sides of the film are irradiated with ultraviolet light at a wavelength of 365 nm and an irradiance of 10 mW / cm² for 15 minutes each, causing crosslinking polymerization of polyethylene glycol diacrylate. The crosslinked film material is peeled off from the release substrate surface and dried at 40°C and a vacuum of 300 Pa for 24 hours to obtain a solid polymer electrolyte membrane. The thickness of this solid polymer electrolyte membrane is approximately 30 μm, and the gel fraction at 25°C is 78%.
[0061] Example 3
[0062] (1) Preparation of the fixed anion-ether oxygen synergistic transport component: A1. Nano-silica with a median particle size of 150 nm was dried at 130 °C and a vacuum of 300 Pa for 3 h. 100 parts by mass of the dried nano-silica were added to a mixture of anhydrous ethanol and deionized water at a mass ratio of 95:5, making the mass ratio of nano-silica to the mixture 1:20. 10 parts by mass of 3-methacryloyloxypropyltrimethoxysilane were added, and the pH of the system was adjusted to 4.8 using a 10% aqueous acetic acid solution. The mixture was reacted at 65 °C and 400 r / min for 5 h. After centrifugation, the nano-silica was washed three times with anhydrous ethanol and dried at 75 °C and a vacuum of 500 Pa for 8 h to obtain modified nano-silica containing surface alkenyl groups.
[0063] A2. 100 parts by mass of the modified nano-silica containing surface alkenyl groups were added to deionized water bubbled with nitrogen for 40 min, so that the mass ratio of the modified nano-silica to deionized water was 1:15. 45 parts by mass of sodium p-styrene sulfonate and 35 parts by mass of polyethylene glycol methyl ether methacrylate with a number average molecular weight of 600 were added, and the mixture was dispersed at 35°C and 500 r / min for 60 min. Nitrogen gas was continued to be introduced, and the system was heated to 70°C. 1.0 part by mass of ammonium persulfate was added, and the graft copolymerization reaction was carried out at 70°C and 400 r / min for 8 h. The mixture was centrifuged and washed with deionized water until the absorbance of the washing liquid at a wavelength of 254 nm was 0.03, to obtain sodium sulfonate-polyether-linked nano-silica.
[0064] A3. The sodium sulfonate-polyether-linked nano-silica was added to a 1.0 mol / L hydrochloric acid aqueous solution, making the mass ratio of sodium sulfonate-polyether-linked nano-silica to hydrochloric acid aqueous solution 1:20. Ion exchange was performed at 40℃ and 300 r / min for 4 h. After centrifugation, the ion exchange operation was repeated once. The nano-silica was washed with deionized water until the chloride ion mass fraction in the washing solution was 0.004%, to obtain hydrogen sulfonate-polyether-linked nano-silica. The hydrogen sulfonate-polyether-linked nano-silica was dispersed in deionized water, and a 0.5 mol / L lithium hydroxide aqueous solution was added dropwise at 40℃ and 300 r / min until the pH of the system reached 7.2. The mixture was stirred for 4 h, centrifuged, washed with deionized water, and dried at 80℃ and 300 Pa for 12 h to obtain the fixed anion-ether oxygen synergistic transport component. The content of lithium sulfonate groups in the fixed anion-ether oxygen synergistic transport component was determined to be 0.99 mmol / g, and the molar ratio of polyether oxygen atoms to lithium sulfonate groups in the ion transport layer was approximately 2.9:1.
[0065] (2) Preparation of solid polymer electrolytes: S1. Polyethylene oxide with a number average molecular weight of 1 million, polyvinylidene fluoride-hexafluoropropylene copolymer with a hexafluoropropylene structural unit mass fraction of 20%, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and the above-mentioned fixed anionic-ether oxygen synergistic transport component were dried at 80°C and a vacuum degree of 300 Pa for 12 h.
[0066] S2. Add 60 parts by mass of polyethylene oxide and 40 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer to a mixed solvent composed of N,N-dimethylformamide and acetonitrile in a mass ratio of 1:1.5, so that the total mass fraction of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is 18%. Stir at 60°C and 400 r / min for 4 h to obtain a polymer solution.
[0067] S3. Add 45 parts by mass of lithium bis(trifluoromethanesulfonyl)imide, 4 parts by mass of lithium difluorooxalateborate, and 18 parts by mass of succinic anion to the polymer solution and stir for 2 hours at 60°C and 400 r / min. Add 18 parts by mass of the above-mentioned fixed anionic-ether oxygen synergistic transport component, stir at 1200 r / min for 60 min, then ultrasonically disperse at 600 W and 45 kHz for 20 min. Then add 12 parts by mass of polyethylene glycol diacrylate with a number average molecular weight of 400 and 0.50 parts by mass of 2-hydroxy-2-methyl-1-phenylpropanone, and stir at 500 r / min for 30 min under light-protected conditions to obtain an electrolyte slurry. The mass ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalateborate is 11.25:1, and the ratio of the total molar amount of lithium ions contained in lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate to the total molar amount of polyether oxygen atoms in the solid polymer electrolyte is 1:7.4.
[0068] S4. The electrolyte slurry is coated onto the surface of a polyethylene terephthalate release substrate, with a wet film thickness of 500 μm, and dried at 55°C for 4 hours. Under nitrogen protection, both sides of the film are irradiated with ultraviolet light at a wavelength of 365 nm and an irradiance of 30 mW / cm² for 5 minutes each, causing crosslinking polymerization of polyethylene glycol diacrylate. The crosslinked film material is peeled off from the release substrate surface and dried at 50°C and a vacuum of 200 Pa for 12 hours to obtain a solid polymer electrolyte membrane. The thickness of this solid polymer electrolyte membrane is approximately 100 μm, and the gel fraction at 25°C is 93%.
[0069] Example 4
[0070] (1) Preparation of the fixed anion-ether oxygen synergistic transport component: A1. Nano-silica with a median particle size of 80 nm was dried at 115 °C and a vacuum of 500 Pa for 4 h. 100 parts by mass of the dried nano-silica were added to a mixture of anhydrous ethanol and deionized water at a mass ratio of 95:5, making the mass ratio of nano-silica to the mixture 1:18. Six parts by mass of 3-methacryloyloxypropyltrimethoxysilane were added, and the pH of the system was adjusted to 4.6 using a 10% aqueous acetic acid solution. The mixture was reacted at 58 °C and 500 r / min for 4.5 h. After centrifugation, the nano-silica was washed three times with anhydrous ethanol and dried at 65 °C and a vacuum of 1000 Pa for 10 h to obtain modified nano-silica containing surface alkenyl groups.
[0071] A2. 100 parts by mass of the modified nano-silica containing surface alkenyl groups were added to deionized water bubbled with nitrogen for 25 min, so that the mass ratio of the modified nano-silica to deionized water was 1:10. 30 parts by mass of sodium p-styrene sulfonate and 25 parts by mass of polyethylene glycol methyl ether methacrylate with a number average molecular weight of 550 were added, and the mixture was dispersed at 28°C and 600 r / min for 50 min. Nitrogen gas was continued to be introduced, and the system was heated to 68°C. 0.6 parts by mass of ammonium persulfate were added, and the graft copolymerization reaction was carried out at 68°C and 450 r / min for 7 h. The mixture was centrifuged and washed with deionized water until the absorbance of the washing liquid at a wavelength of 254 nm was 0.04, to obtain sodium sulfonate-polyether-linked nano-silica.
[0072] A3. The sodium sulfonate-polyether-linked nano-silica was added to a 0.9 mol / L hydrochloric acid aqueous solution, making the mass ratio of sodium sulfonate-polyether-linked nano-silica to hydrochloric acid aqueous solution 1:12. Ion exchange was performed at 30℃ and 350 r / min for 3 h. After centrifugation, the ion exchange operation was repeated once. The nano-silica was washed with deionized water until the chloride ion mass fraction in the washing solution was 0.006%, to obtain hydrogen sulfonate-polyether-linked nano-silica. The hydrogen sulfonate-polyether-linked nano-silica was dispersed in deionized water, and a 0.4 mol / L lithium hydroxide aqueous solution was added dropwise at 30℃ and 350 r / min until the pH of the system reached 7.1. The mixture was stirred for 3 h, centrifuged, washed with deionized water, and dried at 75℃ and 500 Pa for 18 h to obtain the fixed anion-ether oxygen synergistic transport component. The content of lithium sulfonate groups in the fixed anion-ether oxygen synergistic transport component was determined to be 0.90 mmol / g, and the molar ratio of polyether oxygen atoms to lithium sulfonate groups in the ion transport layer was approximately 3.0:1.
[0073] (2) Preparation of solid polymer electrolytes: S1. Polyethylene oxide with a number average molecular weight of 800,000, polyvinylidene fluoride-hexafluoropropylene copolymer with a hexafluoropropylene structural unit mass fraction of 15%, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and the above-mentioned fixed anionic-ether oxygen synergistic transport component were dried at 75°C and a vacuum degree of 400 Pa for 16 h.
[0074] S2. Add 75 parts by mass of polyethylene oxide and 25 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer to a mixed solvent composed of N,N-dimethylformamide and acetonitrile in a mass ratio of 1:1.2, so that the total mass fraction of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is 15%. Stir at 55°C and 500 r / min for 5 h to obtain a polymer solution.
[0075] S3. Add 30 parts by mass of lithium bis(trifluoromethanesulfonyl)imide, 3 parts by mass of lithium difluorooxalate borate, and 10 parts by mass of succinic anion to the polymer solution and stir for 3 hours at 55°C and 500 r / min. Add 15 parts by mass of the above-mentioned fixed anionic-ether oxygen synergistic transport component, stir at 1100 r / min for 40 minutes, then ultrasonically disperse at 500 W and 42 kHz for 25 minutes. Then add 10 parts by mass of polyethylene glycol diacrylate with a number average molecular weight of 800 and 0.40 parts by mass of 2-hydroxy-2-methyl-1-phenylpropanone, and stir at 450 r / min for 40 minutes under light-protected conditions to obtain an electrolyte slurry. The mass ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalateborate is 10:1, and the ratio of the total molar amount of lithium ions contained in lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate to the total molar amount of polyether oxygen atoms in the solid polymer electrolyte is 1:13.6.
[0076] S4. The electrolyte slurry is coated onto the surface of a polyethylene terephthalate release substrate, with a wet film thickness of 500 μm, and dried at 48°C for 5 hours. Under nitrogen protection, both sides of the film are irradiated with ultraviolet light at a wavelength of 365 nm and an irradiance of 25 mW / cm² for 8 minutes each, causing crosslinking polymerization of polyethylene glycol diacrylate. The crosslinked film material is peeled off from the release substrate surface and dried at 48°C and a vacuum of 200 Pa for 15 hours to obtain a solid polymer electrolyte membrane. The thickness of this solid polymer electrolyte membrane is approximately 70 μm, and the gel fraction at 25°C is 90%.
[0077] Example 5
[0078] Solid-state lithium battery fabrication: (1) Preparation of positive electrode sheet: 85 parts by mass of lithium iron phosphate, 7 parts by mass of conductive carbon black, 5 parts by mass of polyvinylidene fluoride binder and 8 parts by mass of electrolyte slurry prepared according to steps S1-S3 in Example 1 (the amount of electrolyte slurry is based on the mass of non-volatile components in the slurry) are added to N-methylpyrrolidone and stirred evenly to obtain positive electrode slurry. The positive electrode slurry is coated on the surface of aluminum foil and dried at 60°C and 400 Pa for 2 hours. Then, under nitrogen protection, it is irradiated with a wavelength of 365 nm and an intensity of 20 mW / cm². 2 The coating is irradiated with ultraviolet light on both sides for 10 minutes to crosslink and polymerize the polyethylene glycol diacrylate in the coating. Then it is dried at 110°C and 400 Pa vacuum for 10 hours. After rolling and cutting, the positive electrode sheet is obtained. The areal capacity of the positive active material layer in the positive electrode sheet is 1.6 mAh / cm². The negative electrode sheet is a lithium metal sheet.
[0079] (2) Battery assembly: B1. Dry the positive electrode at 110°C and 400 Pa for 12 hours, dry the solid polymer electrolyte membrane prepared in Example 1 at 45°C and 200 Pa for 10 hours, and use the lithium metal sheet directly in a dry environment with a dew point not higher than -40°C; B2. Stack the positive electrode, solid polymer electrolyte membrane and lithium metal sheet in the order of -45°C in a dry environment, so that the solid polymer electrolyte membrane covers the positive electrode active material layer and the lithium metal layer; B3. Hot press the stacked positive electrode, solid polymer electrolyte membrane and lithium metal sheet at 70°C and 5 MPa for 10 minutes to obtain the battery cell; B4. In a dry environment with a dew point of -45°C, put the battery cell into an aluminum-plastic film package and seal it, and let it stand at 55°C for 8 hours to obtain a solid lithium battery. The solid-state lithium batteries of Comparative Examples 1-12 were all assembled using the solid polymer electrolyte membranes prepared in the corresponding comparative examples, according to the method of this embodiment.
[0080] Comparative Example 1 The only difference between this comparative example and Example 1 is that no fixed anionic-ether oxygen synergistic transport component is added during the preparation of the solid polymer electrolyte; the amounts of other components and the preparation steps are the same as in Example 1.
[0081] Comparative Example 2 The only difference between this comparative example and Example 1 is that in the preparation of the solid polymer electrolyte, the amount of the fixed anion-ether oxygen synergistic transport component is 24 parts by mass, while the amounts of other components and the preparation steps are the same as in Example 1.
[0082] Comparative Example 3 The only difference between this comparative example and Example 1 is that the amount of lithium bis(trifluoromethanesulfonyl)imide used in the preparation of the solid polymer electrolyte is 15 parts by mass, while the amounts of other components and the preparation steps are the same as in Example 1.
[0083] Comparative Example 4 The only difference between this comparative example and Example 1 is that the amount of lithium bis(trifluoromethanesulfonyl)imide used in the preparation of the solid polymer electrolyte is 55 parts by mass, while the amounts of other components and the preparation steps are the same as in Example 1.
[0084] Comparative Example 5 The only difference between this comparative example and Example 1 is that lithium difluorooxalate borate is not added during the preparation of the solid polymer electrolyte, while the amounts of other components and the preparation steps are the same as in Example 1.
[0085] Comparative Example 6 The only difference between this comparative example and Example 1 is that succinic anion is not added during the preparation of the solid polymer electrolyte, while the amounts of other components and the preparation steps are the same as in Example 1.
[0086] Comparative Example 7 The only difference between this comparative example and Example 1 is that in the preparation of the solid polymer electrolyte, the amount of polyethylene glycol diacrylate used is 2 parts by mass, while the amounts of other components and the preparation steps are the same as in Example 1.
[0087] Comparative Example 8 The only difference between this comparative example and Example 1 is that in the preparation of the solid polymer electrolyte, the amount of polyethylene glycol diacrylate used is 15 parts by mass, while the amounts of other components and the preparation steps are the same as in Example 1.
[0088] Comparative Example 9 The only difference between this comparative example and Example 1 is that no photoinitiator is added during the preparation of the solid polymer electrolyte, while the amounts of other components and the preparation steps are the same as in Example 1.
[0089] Comparative Example 10 The only difference between this comparative example and Example 1 is that 12 parts by mass of the fixed anionic-ether oxygen synergistic transport component are replaced with a physical blend of lithium p-styrene sulfonate and polyethylene glycol methyl ether (number average molecular weight 500), wherein lithium p-styrene sulfonate is 1.9 parts by mass and polyethylene glycol methyl ether is 1.8 parts by mass. Additionally, 8.3 parts by mass of the modified nano-silica containing surface alkenyl groups prepared in step A1 of Example 1 are added. The above amounts are determined based on the lithium sulfonate group content of 0.85 mmol / g and the content of grafted polyether side chains in the 12 parts by mass of the fixed anionic-ether oxygen synergistic transport component. The amounts of other components and the preparation steps are the same as in Example 1. The total mass of the substitute is 12 parts by mass, changing only the grafting structure.
[0090] Comparative Example 11 The only difference between this comparative example and Example 1 is that polyethylene glycol methyl ether methacrylate is not added during the preparation of the fixed anionic-ether oxygen synergistic conductive component; the amounts of other raw materials and preparation steps are the same as in Example 1. 12 parts by mass of the modified nano-silica without polyether side chains were used in the preparation of the solid polymer electrolyte; the amounts of other components and preparation steps were the same as in Example 1.
[0091] Comparative Example 12 The only difference between this comparative example and Example 1 is that: in the preparation of the solid polymer electrolyte, polyvinylidene fluoride-hexafluoropropylene copolymer is not added, the amount of polyethylene oxide is 100 parts by mass, and the amounts of other components and preparation steps are the same as in Example 1.
[0092] Performance testing: The solid polymer electrolyte membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 12, and the solid lithium batteries assembled using the above-mentioned solid polymer electrolyte membranes according to the method of Example 5 (all positive electrode active materials are lithium iron phosphate, all negative electrodes are lithium metal sheets, and the areal capacity of the positive electrode active material layer is 1.6 mAh / cm2) were subjected to the following performance tests: Before the test, all electrolyte membranes were dried at 45°C and a vacuum degree not exceeding 300 Pa until the moisture content measured by Karl Fischer method was not higher than 500 ppm and the total residual amount of N,N-dimethylformamide and acetonitrile measured by headspace gas chromatography was not higher than 1000 ppm; except for the rate performance test, each test used 3 parallel samples and the average value was taken.
[0093] 1. Ionic Conductivity Test: A solid polymer electrolyte membrane was cut into 16mm diameter discs and sandwiched between two stainless steel blocking electrodes to assemble a CR2032 coin cell. AC impedance spectroscopy was performed using an electrochemical workstation with a frequency range of 0.1Hz to 1MHz and an AC amplitude of 10mV. Tests were conducted after holding the cells at 25℃ and 60℃ for 2 hours respectively. The ionic conductivity was calculated using the formula σ = L / (R×A), where L is the electrolyte membrane thickness, R is the bulk resistance, and A is the effective electrode area.
[0094] 2. Lithium-ion transference number test: A symmetrical battery was assembled using a combination of DC polarization and AC impedance spectroscopy. A 10mV DC polarization voltage was applied, and the current values and AC impedance spectra before and after polarization were measured to calculate the lithium-ion transference number. When the rate of change of polarization current within 1 hour was not higher than 1%, the steady-state current Iss was taken and calculated according to tLi+=Iss(ΔV-I0R0) / [I0(ΔV-IssRss)], where I0 and Iss are the initial current and steady-state current, respectively, R0 and Rss are the interface resistances before polarization and at steady state, respectively, and ΔV is the DC polarization voltage.
[0095] 3. Electrochemical stability window test: Using aluminum foil as the working electrode and lithium sheet as the counter electrode and reference electrode, a linear scan voltammetry test was performed at 25℃ with a scan rate of 1mV / s to determine the oxidation decomposition potential.
[0096] 4. Tensile Strength Test: The solid polymer electrolyte membrane was cut into dumbbell-shaped specimens and tested on a universal testing machine at a tensile rate of 10 mm / min. The breaking strength was recorded. The parallel section width of the dumbbell-shaped specimen was 4 mm and the gauge length was 20 mm. The cross-sectional area was calculated based on the measured membrane thickness, and the test was conducted in an environment with a dew point not higher than -40°C.
[0097] 5. Cyclic Performance Test: The solid-state lithium battery was subjected to constant current charge-discharge cycle test at 0.5C rate under 60℃ conditions. The charging cut-off voltage was 3.8V and the discharging cut-off voltage was 2.5V. The capacity retention rate after 100 cycles was recorded. Before the test, two cycles of formation were performed at 0.1C. During the cycle, a constant surface pressure of 0.5MPa was maintained on the cell.
[0098] 6. Rate Performance Testing: The solid-state lithium batteries prepared in Example 1 and Comparative Example 1 were subjected to constant current charge-discharge tests at 25°C at rates of 0.2C, 0.5C, 1C, 2C, and 0.2C, respectively, and the discharge specific capacity at each rate was recorded. Each rate was tested for 5 consecutive cycles, and a constant surface pressure of 0.5MPa was maintained on the cell during the test.
[0099] 7. Gel fraction test: Weigh the dried electrolyte membrane by mass m0, immerse it in sufficient anhydrous acetonitrile at 25℃ for 24 hours, replacing the acetonitrile every 8 hours; after removal, dry it to constant weight at 60℃ and a vacuum degree not exceeding 500Pa, and weigh it again to obtain mass m1. Calculate the gel fraction G according to the formula: G = m1 / m0 × 100%. This gel fraction is the total insoluble mass fraction of the membrane measured under the above acetonitrile extraction conditions. The test uses 3 parallel samples and the average value is taken.
[0100] The performance test results are shown in Tables 1 and 2.
[0101] Table 1. Performance test results of solid polymer electrolyte and solid lithium battery
[0102] Note: Gel fraction was determined by acetonitrile extraction at 25℃.
[0103] Table 2. Test results of rate performance of solid-state lithium batteries (discharge specific capacity, mAh / g)
[0104] As shown in Table 1, the embodiments of the present invention outperform most comparative examples in key indicators such as ionic conductivity, lithium-ion transport number, electrochemical window, tensile strength, and cycle capacity retention, demonstrating the synergistic superiority of composition and structural design. Specifically, the absence or deviation in the amount of the fixed anion-ether oxygen synergistic transport component, insufficient or excessive lithium salt, omission of lithium difluorooxalate borate or succinate, insufficient or excessive crosslinking agent, absence of photoinitiator, and substitution of the synergistic component of the present invention with a physical blend or a component with an incomplete structure all lead to varying degrees of decreased ionic conductivity, poorer interfacial stability, or impaired mechanical strength. Among them, Comparative Example 1, due to the complete absence of the synergistic transport component, shows a particularly significant decrease in transport number and rate performance. Comparative Example 9, due to insufficient crosslinking caused by the absence of a photoinitiator, shows a significant reduction in tensile strength and cycle capacity retention. Comparative Example 12, due to the absence of a copolymer, exhibits poor overall performance. These comparisons indicate that the synergistic combination of components and the introduction of a specific core-graft structure are key to achieving a balance between high conductivity, high transport number, and good mechanical properties.
[0105] As shown in Table 2, as the discharge rate gradually increases from 0.2C to 2C, the discharge specific capacity of all samples shows a decreasing trend. However, the capacity decay of Example 1 is significantly smaller, and it still maintains a high capacity output at high rates. When the rate recovers to 0.2C, the capacity recovery rate of Example 1 is significantly better than that of Comparative Example 1, indicating that its ion conduction kinetics are better, its polarization is lower, and its electrolyte structure can still maintain good stability and reversibility after high-rate charge and discharge.
[0106] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A solid polymer electrolyte membrane, characterized in that, The total mass of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer in the solid polymer electrolyte membrane raw material is 100 parts, of which 60-80 parts by mass of polyethylene oxide and 20-40 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer are included. It also includes the following components by mass: 25-45 parts of lithium bis(trifluoromethanesulfonyl)imide, 6-18 parts of succinic anion, 5-12 parts of polyethylene glycol diacrylate, 0.15-0.50 parts of photoinitiator, 1-4 parts of lithium difluorooxalate borate, and 6-18 parts of fixed anion-ether oxygen synergistic transport component. The method for preparing the solid polymer electrolyte membrane includes the following steps: S1. The polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and the fixed anionic-ether oxygen synergistic transport component are dried at 60-80℃ and under a vacuum degree not exceeding 500Pa for 12-24h respectively. S2. According to the above-defined mass fractions, add polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer to a mixed solvent composed of N,N-dimethylformamide and acetonitrile in a mass ratio of 1:0.8-1:1.5, so that the total mass fraction of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is 8%-18%, and stir at 45-60℃ and 400-700r / min for 4-8h to obtain a polymer solution; S3. Lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, and succinate are added to the polymer solution and stirred at 45-60℃ and 400-700 r / min for 2-4 h. The fixed anionic-ether oxygen synergistic transport component is added and ultrasonically dispersed at 300-600 W and 35-45 kHz for 20-40 min. Then, polyethylene glycol diacrylate and a photoinitiator are added and stirred at 300-500 r / min for 30-60 min under light-protected conditions to obtain an electrolyte slurry. S4. The electrolyte slurry is coated onto the surface of the release substrate, with a wet film thickness of 150-500 μm, and dried at 40-55℃ for 4-8 hours; under nitrogen protection, irradiation is performed using a wavelength of 365 nm and an irradiation intensity of 10-30 mW / cm². 2 The membrane is irradiated with ultraviolet light for 5-15 minutes on both sides to induce cross-linking polymerization of polyethylene glycol diacrylate. The cross-linked membrane material is then peeled off from the release substrate and dried at 40-50°C and a vacuum degree not exceeding 300Pa for 12-24 hours to obtain a solid polymer electrolyte membrane. The preparation method of the fixed anion-ether oxygen synergistic transport component includes the following steps: A1. Dry nano-silica at 110-130℃ and a vacuum degree not exceeding 500Pa for 3-5 hours. Add 100 parts by weight of the dried nano-silica to a mixture of anhydrous ethanol and deionized water in a mass ratio of 95:5, so that the mass ratio of nano-silica to the mixture is 1:10-1:
20. Add 5-10 parts by weight of 3-methacryloyloxypropyltrimethoxysilane. Adjust the pH of the system to 4.2-4.8 with a 10% aqueous acetic acid solution. React at 55-65℃ and 400-700 r / min for 3-5 hours. After centrifugation, wash three times with anhydrous ethanol and dry at 60-75℃ and a vacuum degree not exceeding 1000Pa for 8-12 hours to obtain modified nano-silica containing surface alkenyl groups. A2. Add 100 parts by weight of the modified nano-silica containing surface alkenyl groups to deionized water bubbled with nitrogen for 20-40 min, so that the mass ratio of the modified nano-silica to deionized water is 1:8-1:
15. Add 25-45 parts by weight of sodium p-styrene sulfonate and 20-35 parts by weight of polyethylene glycol methyl ether methacrylate. Disperse at 25-35℃ and 500-800 r / min for 30-60 min. Continue to purge with nitrogen and heat the system to 60-70℃. Add 0.5-1.0 parts by weight of ammonium persulfate. Carry out the graft copolymerization reaction at 60-70℃ and 400-600 r / min for 4-8 h. Centrifuge and wash with deionized water until the absorbance of the washing solution at 254 nm wavelength is not higher than 0.05 to obtain sodium sulfonate-polyether-linked nano-silica. A3. Add the sodium sulfonate-polyether-linked nano-silica to a 0.5-1.0 mol / L hydrochloric acid aqueous solution, making the mass ratio of sodium sulfonate-polyether-linked nano-silica to hydrochloric acid aqueous solution 1:10-1:
20. Perform ion exchange at 25-40℃ and 300-500 r / min for 2-4 hours. After centrifugation, repeat the ion exchange operation once. Wash with deionized water until the chloride ion mass fraction in the washing solution is no higher than 0.01%, to obtain hydrogen sulfonate-polyether chain. Grafted nano-silica: The sulfonate-type polyether-linked nano-silica is dispersed in deionized water, and a lithium hydroxide aqueous solution with a concentration of 0.1-0.5 mol / L is added dropwise at 25-40℃ and 300-500 r / min until the pH of the system is 6.5-7.
5. The mixture is stirred for 2-4 h, centrifuged and washed with deionized water, and dried at 60-80℃ and a vacuum degree not exceeding 500 Pa for 12-20 h to obtain the fixed anion-ether oxygen synergistic transport component.
2. The solid polymer electrolyte membrane according to claim 1, characterized in that, The number average molecular weight of the polyethylene oxide is 300,000 to 1,000,000; The mass fraction of hexafluoropropylene structural units in the polyvinylidene fluoride-hexafluoropropylene copolymer is 8%-20%; The number average molecular weight of the polyethylene glycol diacrylate is 400-1000; The number-average molecular weight of the polyethylene glycol methyl ether methacrylate is 400-600.
3. The solid polymer electrolyte membrane according to claim 1, characterized in that, The photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone; The mass ratio of lithium bis(trifluoromethanesulfonylimide) to lithium difluorooxalateborate is 8:1-25:1; The ratio of the total molar amount of lithium ions contained in the lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate to the total molar amount of ether oxygen atoms contained in the polyethylene oxide in the solid polymer electrolyte membrane is 1:7 to 1:
20.
4. The solid polymer electrolyte membrane according to claim 1, characterized in that, The content of lithium sulfonate groups in the fixed anion-ether oxygen synergistic transport component is 0.40-1.20 mmol / g.
5. The solid polymer electrolyte membrane according to claim 1, characterized in that, After adding the fixed anionic-ether oxygen synergistic transport component in step S3, stir at 800-1200 r / min for 30-60 min, and then perform ultrasonic dispersion; the thickness of the solid polymer electrolyte membrane obtained in step S4 is 30-120 μm.
6. A solid-state lithium battery, characterized in that, The device includes a positive electrode, a negative electrode, and a solid polymer electrolyte membrane disposed between the positive electrode and the negative electrode. The solid polymer electrolyte membrane is the solid polymer electrolyte membrane according to any one of claims 1-5. The positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The negative electrode includes a negative current collector and a negative active material layer or a lithium metal layer disposed on the surface of the negative current collector.
7. A method for preparing a solid-state lithium battery as described in claim 6, characterized in that, Includes the following steps: B1. Dry the positive electrode and negative electrode at 80-120℃ and a vacuum degree not exceeding 500Pa for 8-16 hours respectively, and dry the solid polymer electrolyte membrane at 40-50℃ and a vacuum degree not exceeding 300Pa for 8-12 hours; when the negative electrode active material layer of the negative electrode is a lithium metal layer, the lithium metal sheet is not dried and can be used directly in a dry environment with a dew point not exceeding -40℃. B2. In a dry environment with a dew point not higher than -40°C, the positive electrode sheet, the solid polymer electrolyte membrane, and the negative electrode sheet are stacked in the order of positive electrode sheet, solid polymer electrolyte membrane covering the positive electrode active material layer and the negative electrode active material layer or the lithium metal layer. B3. The stacked positive electrode, solid polymer electrolyte membrane and negative electrode are hot-pressed at 60-90℃ and 2-8MPa for 5-20 minutes to obtain the battery cell. B4. In a dry environment with a dew point not higher than -40°C, the battery cell is placed into a battery casing or aluminum-plastic film packaging and sealed. It is then left to stand at 45-65°C for 6-12 hours to obtain a solid-state lithium battery.
Citation Information
Patent Citations
Electrolyte for lithium polymer batteries
CN101897071A
Composite solid polymer electrolyte membrane and preparation method and application thereof
CN111540948A
